مراحل تطور مدرسة التفيض الأهلية 1919- 1939 (Journal of the College of Basic Education, 2024)
Since its establishment, Al-Tafayudh Private School had played a significantrole in the Iraqi student movement, the development of events in the country and the growing national awareness, as well as the guidance of the rational religious authority, which motivated the students to contribute more to the struggle of our people against colonial control and against the unjust treaties concluded by the Iraqi government with Britain, it also played a Prominent role in overthrowing the reactionary government of Yassin al-Hashemi after supporting the national coup that overthrew it, worth to note that the roles of the student movement had ranged from protests, demonstrations, to mass strikes of a general patriotic nature.On the other hand, Al-Tafayudh Private school had sought to keep pace with the laws and regulations of the Ministry of Education in order to improve the educational process, which made it stand in the ranks of modern model schools, it was able to graduate a constellation of the best men who served their country in all fields.